Selection and recruitment of candidates for primary teacher training in Asian countries - Gunasekera, Yapawannaku R. M. S. K. 1927- ([Quezon City s.n.], 1963)
This paper presents the details in selection and recruitment practices concerning the candidates for primary teacher training in the thirteen Asian countries represented at the UNESCO Regional Center. Suggestions based in part on the study for a selection and recuitment program to be adopted in Ceylon were also offered in this study.
Thesis (M.Ed.)--University of the Philippines
Keywords: Teachers -- Selection and appointment; Teachers -- Asia